ChemInform Abstract: Harmony of CdI2 with CuBr for the One‐Pot Synthesis of Optically Active α‐Allenols. Issue 29 (July 2015) - Zhang, Jiasheng; Ye, Juntao; Ma, Shengming
Abstract Terminal propargylic alcohols react with in situ generated imines in the presence of a chiral ligand and both CuBr and CdI2 towards optically active allenols.